DCE replacement strategies - Johner, Heinz (IBM redbooks., 2003)
This IBM Redbooks publication recommends strategies that you can use to replace the Distributed Computing Environment (DCE) dependencies in your environment and move to new technologies. The following topics are covered: - DCE overview and recap - Replacement technologies - Replacement strategies - Replacement scenarios - Replacement coding examples This book is a valuable information source if you are an executive, administrator, or developer of an IBM customer environment that uses IBM DCE for a distributed systems and application infrastructure. Although strategies for replacing DCE are described, the book does not cover strategies for replacing dependencies to IBM products that use DCE, such as DFS and TXSeries. Please note that the additional material referenced in the text is not available from IBM.